Chinese Herbal Medicines as Potential Agents for Alleviation of Heat Stress in Poultry. (31st October 2017) - Shokryazdan, Parisa; Jahromi, Mohammad Faseleh; MD Saadand, Salwani; Ebrahimi, Mahdi; Idrus, Zulkifli; Zhou, Hailong; Diao, Xiao Ping; Liang, Juan Boo
Abstract : Heat stress negatively affects the productivity of chickens in commercial poultry farms in humid tropics. In this study, the concentrations and types of the antioxidant compounds of eight Chinese herbal medicines, which have previously demonstrated promising effects on suppressing heat stress as a mixture, were investigated using reversed-phase High Performance Liquid Chromatography, spectrophotometry, Liquid Chromatography Mass Spectrometry, and Gas-Liquid Chromatography. Our results provided the levels of phenolic compounds, total amounts of sugars, and total unsaturated fatty acids in the herbal extracts. Apart from the detection and quantification of the active ingredients of herbs that have the potential to mitigate heat stress in poultry, results of this study also provide useful data for developing an efficient and accurate formulation of the herbs' mixtures in order to induce positive effects against heat stress in in vivo studies.